TEOLOGI ADHI BUDHA DALAM ALIRAN BUDHA MAHAYANA - Yadain, Zul (P3M STAIN Sorong, 2016)
Buddhism starts from the fact that people experience in their lives. Teachings starts not from the transcendent, the question about God and his relationship with the universe and everything in it, it starts by explaining the suffering. In some texts Pali and Sanskrit mentioned that, the Buddha is always silent when asked his followers about God, but always insisted that practice moral principle divinity if we study his teachings contained in the scriptures of Tripitaka, it will get the concept of God that is different from the concept of God in other religions. Posts, in this article talking about Buddhism Mahayana gives positive ideas about God, the soul and destiny. The Mahayana gives all human beings salvation of the world through faith, love, and knowledge. Mahayana is more emphasis on love and safety intentions of each creature, and find the reality in Nirvana, which is âvoidâ in the sense that is free from limits or empirical knowledge that we have. In addition, the followers of Mahayana Buddhism found not shut his eyes to the world when it reached Nirvana, but offers a light for the world to reach the goal.